Reconfigurable microfluidic circuits for isolating and retrieving cells of interest - Deroy, C; Wheeler, JHR; Rumianek, AN; Cook, PR; Durham, WM; Foster, KR; Walsh, EJ (American Chemical Society, 2022)
Microfluidic devices are widely used in many fields of biology, but a key limitation is that cells are typically surrounded by solid walls, making it hard to access those that exhibit a specific phenotype for further study. Here, we provide a general and flexible solution to this problem that exploits the remarkable properties of microfluidic circuits with fluid walls─transparent interfaces between culture media and an immiscible fluorocarbon that are easily pierced with pipets. We provide two proofs of concept in which specific cell subpopulations are isolated and recovered: (i) murine macrophages chemotaxing toward complement component 5a and (ii) bacteria (Pseudomonas aeruginosa) in developing biofilms that migrate toward antibiotics. We build circuits in minutes on standard Petri dishes, add cells, pump in laminar streams so molecular diffusion creates attractant gradients, acquire time-lapse images, and isolate desired subpopulations in real time by building fluid walls around migrating cells with an accuracy of tens of micrometers using 3D printed adaptors that convert conventional microscopes into wall-building machines. Our method allows live cells of interest to be easily extracted from microfluidic devices for downstream analyses.